(untitled) (RIAF. International Journal of Physical Activity, 2024)
The methodical conception regarding historical research in sports remains absent in the current models utilized by researchers. Diverse opinions on how to draft the final report of events, facts, pastimes, outcomes, narratives, discoveries, among others, have sparked considerable debate. However, a concrete or appropriate model or methodology to guide historians in organizing their ideas has yet to be developed. Each historian, based on their experience, applies investigative methods and techniques from a social and historical perspective to construct their written arguments. In this context, it is evident that educational, didactic, social, historical, and political models, among others, still fall short of the desired outcomes for this type of research. This study contributes methodological aspects that enable the development of historical research in the field of sports, utilizing periods and stages, bibliographic materials (both digital and printed), as well as the study of sports icons and personalities. These elements allow for the systematization and organization of key milestones in this pastime, which deserve to be studied in depth.